Emerging dimensions of technology management - Akhilesh, K.B (Springer India, 2013)
Technology is the key driver of business. May it be airport, ICT , smart governance, manufacturing or plantations. Technology management opens up opportunities for the business and helps achieve leadership positions. This collection of papers provide a glimpse of issues faced in different sectors. These papers will also help inspire more researchers to expand the scope of the subject itself.